Continued growth after fixation of slipped capital femoral epiphysis. (December 2016) - Holmdahl, Per; Backteman, Torsten; Danielsson, Aina; Kärrholm, Johan; Riad, Jacques
Purpose: When treating slipped capital femoral epiphysis (SCFE), a smooth pin with a hook or a short threaded screw can be used to allow further growth, which could be important to prevent the development of impingement and early arthritis. The purpose of this investigation was to measure growth in three dimensions after fixation of SCFE. Methods: Sixteen participants with unilateral SCFE, nine girls and seven boys with a median age of 12.0 years (range 8.4–15.7 years), were included. The slipped hip was fixed with a smooth pin with a hook, and the non-slipped hip was prophylactically pinned. At the time of surgery, tantalum markers were installed bilaterally on each side of the growth plate through the drilled hole for the pin. Examination with radiostereometric analysis (RSA) was performed postoperatively and at 3, 6 and 12 months. The position of the epiphysis in relation to the metaphysis was calculated. Results: At 12 months, the epiphysis moved caudally, median 0.16 mm and posteriorly 2.28 mm on the slipped side, in comparison to 2.28 cranially and 0.91 mm posteriorly on the non-slipped side, p = 0.003 and p = 0.030, respectively. Both slipped and non-slipped epiphysis moved medially, 1.52 and 1.74 mm, respectively. A marked variation in the movement was noted, especially on the slipped side. Conclusions: The epiphysis moved in relation to the metaphysis after smooth pin fixation, both on the slipped side and on the prophylactically fixed non-slipped side, implying further growth. The RSA method can be used to understand remodelling after 'growth-sparing' fixation of SCFE.